Tics and Tourette’s syndrome - Shivam Om Mittal (Drugs in Context, 2020)
Tics and Tourette’s syndrome are common hyperkinetic movement disorders seen mostly in the pediatric age group. Tics are defined as sudden, rapid, recurrent, nonrhythmic motor movements or vocalization, generally preceded by urge. Tourette’s syndrome is defined as the presence of both motor and phonic tics for more than 1 year in patients with onset less than 18 years old. Most of these hyperkinetic movement disorders improve in adulthood. This review emphasizes the clinical pearls in the diagnosis and distinguishing it from other movement disorders. The treatment ranges from behavioral therapies, medical management, and also surgical treatment such as deep brain stimulation that is limited to refractory patients.